The arthritis-associated HLA-B*27:05 allele forms more cell surface B27 dimer and free heavy chain ligands for KIR3DL2 than HLA-B*27:09. - Cauli, A; Shaw, J; Giles, J; Hatano, H; Rysnik, O; Payeli, S; McHugh, K; Dessole, G; Porru, G; Desogus, E; Fiedler, S; Hölper, S; et al. (Oxford University Press, 2013)
OBJECTIVES: HLA-B*27:05 is associated with AS whereas HLA-B*27:09 is not associated. We hypothesized that different interactions with KIR immune receptors could contribute to the difference in disease association between HLA-B*27:05 and HLAB*27:09. Thus, the objective of this study was to compare the formation of β2m-free heavy chain (FHC) including B27 dimers (B272) by HLA-B*27:05 and HLA-B*27:09 and their binding to KIR immunoreceptors. METHODS: We studied the formation of HLA-B*27:05 and HLA-B*27:09 heterotrimers and FHC forms including dimers in vitro and in transfected cells. We investigated HLA-B*27:05 and HLA-B*27:09 binding to KIR3DL1, KIR3DL2 and LILRB2 by FACS staining with class I tetramers and by quantifying interactions with KIR3DL2CD3ε-reporter cells and KIR3DL2-expressing NK cells. We also measured KIR expression on peripheral blood NK and CD4 T cells from 18 HLA-B*27:05 AS patients, 8 HLA-B27 negative and 12 HLA-B*27:05+ and HLA-B*27:09+ healthy controls by FACS staining. RESULTS: HLA-B*27:09 formed less B27₂ and FHC than HLA-B*27:05. HLA-B*27:05-expressing cells stimulated KIR3DL2CD3ε-reporter T cells more effectively. Cells expressing HLA-B*27:05 promoted KIR3DL2+ NK cell survival more strongly than HLA-B*27:09. HLA-B*27:05 and HLA-B*27:09 dimer tetramers stained KIR3DL1, KIR3DL2 and LILRB2 equivalently. Increased proportions of NK and CD4 T cells expressed KIR3DL2 in HLA-B*27:05+ AS patients compared with HLA-B*27:05+, HLA-B*27:09+ and HLA-B27- healthy controls. CONCLUSION: Differences in the formation of FHC ligands for KIR3DL2 by HLA-B*27:05 and HLA-B*27:09 could contribute to the differential association of these alleles with AS.